PERBEDAAN KEMAMPUAN KOMUNIKASI MATEMATIKSISWA ANTARA YANG MENDAPATKAN MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS DENGAN MODEL PEMBELAJARANGUIDED NOTE TAKING - Gesti Pratiwi Sartika; Nitta Puspitasari (Mosharafa: Jurnal Pendidikan Matematika, 2013)
Abstract:Exsperimentwith praeksperiment(the statistic group pretest-posttes design) aimed to find out the defferences ability of mathematic communication student between the students who got “Student Teams Achievement Division” learning model with “Guided Note Taking” learning model. Futhermore, the researcher discovered the attitude of student toward learning mathematics using “Student Teams Achievement Divisions” learning model with “Guided Note Taking” learning model. The result showed that:(1) There is no differences between the communication skills of students mathematic which gain “Student Teams Achievement Divisions”learning model and “Guided Note Taking” learning model, (2) generally students were good using both of learning model. Abstrak:Penelitian eksperimen dengan desain praeksperimen (the statistic group pretest-posttes design) bertujuan untuk mengetahui perbedaan kemampuan komunikasi matematik siswa antara yang mendapatkan model pembelajaran Student Teams Achievement Divisions dengan model pembelajaran Guided Note Taking, serta mengetahui sikap siswa terhadap pembelajaran matematika terhadap model pembelajaran Student Teams Achievement Divisions dengan model pembelajaran Guided Note Taking. Hasil penelitian ini menunjukan bahwa: (1) tidak terdapat perbedaan kemampuan komunikasi matematik siswa antara yang mendapatkan model pembelajaran Student Teams Achievement Divisions dengan model pembelajaran Guided Note Taking; (2) sikap siswa terhadap model pembelajaran Student Teams Achievement Divisions dan model pembelajaran Guided Note Taking secara umum siswa bersikap baik terhadap kedua model pembelajaran tersebut.